PERGESERAN BUDAYA PENUTUR BAHASA DAERAH TONTEMBOAN DALAM SISTEM SOSIAL DI DESA RAANAN LAMA KECAMATAN MOTOLING - Scolastika Sengkey; Maryam Lamadirisi; Hamdi Gugule (Labor Program Studi Pendidikan Sosiologi, 2021)
This research focuses on the forms of cultural shift of speakers of the ‘Tontemboan’ local language. The purpose of this study is to identify and describe the forms of cultural shift of local language speakers from the aspect of time/moment of use the ‘Tontemboan’ local language in Raanan Lama village, subdistrict Motoling. This research use desciptive qualitative approach. Data analysis using literature review in the form of library books and scientific articles that support. The data was obtained from the results of observations and interviews whit the community and government in the village of Raanan Lama, District of Motoling. Currently, the uses of regional languages is only during mourning services and weddings parties where only elderly parents deliver greetings. The culture of speaking local languages in the family and local language lessons at school are not as active as they used to be. In conclusion, the different conditions that occurred at different times have caused a shift in the speech culture of the Tontemboan regional language in the social system in the Raanan Lama Village. The researcher hopes that this research can be useful in future research and related special purposes.